Screening of probiotics with efficient α-glucosidase inhibitory ability and study on the structure and function of its extracellular polysaccharide. (February 2022) - Wang, Jia-Bin; Yu, Le-Yi; Zeng, Xu; Zheng, Jun-Wei; Wang, Bin; Pan, Li
Abstract: Inhibition of α-glucosidase activity is an important strategy in lowering the concentration of blood sugar. In this paper, using domestic and foreign characteristic food-derived substances as the sources of lactobacillus, the performance of them were evaluated by measuring the strains' α-glucosidase inhibitory ability. Finally, the cell-free extracellular supernatants (CFS) of Lactobacillus rhamnosus LB1lac10 was determined to have the highest α-glucosidase inhibition ability. Based on the Nanopore third-generation sequencing technology platform, the genome of LB1lac10 was sequenced and functional gene annotation was performed. After that, the biological activity and structural composition of the exopolysaccharide produced by L. rhamnosus LB1lac10 were studied. The purified exopolysaccharide EPS1-1 also showed efficient α-glucosidase inhibitory ability. The structure and conformation characteristics of EPS1-1 were further analyzed. The EPS1-1 from L. rhamnosus LB1lac10 had a molecular weight of 88, 650 Da, and it was mainly composed of mannose, glucuronic acid, glucose, xylose, galactose, and arabinose. From the FT-IR and NMR analyses, EPS1-1 had functional groups of a typical polysaccharide structure and contained two types of glycosidic bonds with α-configuration pyranose. The main glycosidic bond corresponded to → 4)-α- d -Glcp-(1→, which might be an important reason why EPS1-1 could inhibit α-glycosidase. Thermodynamic studies showed that EPS1-1 had high heat resistance to meet the needs of food processing. The results suggested that L. rhamnosus LB1lac10 could be used as a potential probiotic to lower blood sugar, and the EPS1-1 has the potential to serve as a natural α-glycosidase inhibitor to regulate the concentration of blood glucose. Graphical abstract: The exopolysaccharide of L. rhamnosus LB1lac10, a strain with high-efficiency α-glucosidase inhibitory ability, were isolated and analyzed. Image 1 Highlights: Nine isolated probiotics owned α-glucosidase inhibitory ability and the strain LB1lac10 owned the highest value. Based on the third-generation sequencing technology of the Nanopore platform, the strain LB1lac10 was sequenced and functional gene annotation was performed. The purified exopolysaccharide EPS1-1 from L. rhamnosus LB1lac10 showed ability in inhibiting α-glucosidase activity. The EPS1-1 was mainly composed of mannose, glucuronic acid, glucose, xylose, galactose, and arabinose. The EPS1-1 mainly contained two types of glycosidic bonds with α-configuration pyranose, and the main signal peak of EPS1-1 corresponded to → 4)-α-D-Glcp-(1→.